2022
DOI: 10.1097/01.reo.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Use of Outcome Measures by Certified Lymphedema Therapists With Survivors of Breast Cancer With Breast Cancer–Related Lymphedema

Abstract: Background: Survivors of breast cancer (SBC) with breast cancer–related lymphedema (BCRL) have demonstrated neuromusculoskeletal restrictions, sensorimotor impairments, postural instability, and balance deficits. To date, there have been no studies that investigate outcome measures (OMs) used by certified lymphedema therapists (CLTs) with SBC with BCRL. Objective: The purposes of this study were to (1) determine types of OMs used and their frequency of use by CLTs with SBC with BCRL and their differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 21 publications
(48 reference statements)
0
28
0
Order By: Relevance
“…However, there was high adherence to use of exercise at 87%. A recent report by Doubblestein et al reported that 100% of PTs surveyed reported using volume and circumference measures [29] compared to 49% who use circumference to calculate limb volume in this study. However, Doubblestein et al grouped all circumference and volume measures into one category and did not discern stage of BCRL within their survey and this may explain the large difference between reports.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, there was high adherence to use of exercise at 87%. A recent report by Doubblestein et al reported that 100% of PTs surveyed reported using volume and circumference measures [29] compared to 49% who use circumference to calculate limb volume in this study. However, Doubblestein et al grouped all circumference and volume measures into one category and did not discern stage of BCRL within their survey and this may explain the large difference between reports.…”
Section: Discussionmentioning
confidence: 54%
“…These two sampling methods limited our ability to account for the total number of PTs or PTAs who received the survey, thereby limiting our ability to calculate a survey response rate. Other physical therapy practice pattern surveys report a 2-82% response rate [24,28,29,34]. The second is that we assessed adherence to clinical practice guidelines using a single method, survey.…”
Section: Limitationsmentioning
confidence: 99%
“…An online survey design was implemented to gather responses from CLTs from various postprofessional lymphedema continuing education programs and related professional associations in the United States. Detailed description of the survey methodology, variables, and statistical analysis is provided elsewhere 8. This study is a follow-up analytic investigation to the study by Doubblestein et al,8 which received exempt status by the Health Sciences and Behavioral Sciences Institutional Review Board of the University of Michigan, Flint and from A.T.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was divided into 3 domains to gather (1) demographics and practice characteristics of respondents, (2) levels of use of standardized and clinically relevant OMs, and (3) levels of agreement on facilitators and barriers to using OMs. Outcome measures were separated into 2 domains from the International Classification of Functioning, Disability and Health (ICF): (1) OMs used by CLTs to measure ICF domain of body structures and functions with subdomains of (1.1) joint function, (1.2) flexibility, (1.3) strength, (1.4) volume, (1.5) pain, (1.6) tissue consistency, (1.7) body composition, and (1.8) sensation; and (2) OMs used by CLTs to measure ICF domains of activities and participation with subdomains of (2.1) patient-reported function and health-reported quality of life, (2.2) patient-reported upper quadrant function, (2.3) patient-reported fatigue, (2.4) mobility and balance, and (2.5) upper extremity activity and motor control 8. A total of 92 OMs (see Supplemental Digital Content 1, available at: http://links.lww.com/REHABONC/A46) were scored a level of use by the respondents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation